Adaptation and application of the Algorithm for Inventive Problem Solving in the design of the automatic control system for pumping water station - Jair, Mejia (Otkhody i Resursy, 2023)
The growing demand of visitors to hotels oriented to the ecological and cultural tourism approach represents a challenge for the optimization of water resources, in contrast to traditional hotels, these depend exclusively on water wells. This type of commercial establishment is growing in Latin American countries such as Mexico, El Salvador, Ecuador, as well as in European countries such as Spain. The solution to this problem is of great importance for this type of tourist establishments. The environmental and economic spheres are the most affected due to this problem. This is due to the waste of water and excessive payment for electricity. There are many advantages related to the automation of the pumping system: the ability to save fuel resources, reduce machine wear for maintenance and repair time. This cost and time savings will increase the profits of the hotels, while the workload of the maintenance Department is reduced because the constant monitoring of the water level in the tanks would not be necessary. This article focuses on the specific case of a hotel in the province of La Libertad in El Salvador. The data is analyzed to determine the initial conditions of the technical problem. An algorithm for Inventive Problem Solving is applied in order to develop a system that performs the water supply automatically, receives signals by means of level sensors, starts or stops the pumps (if necessary), and detects water leaks with the use of pressure sensors, reducing the waste of water and electricity.